Finch’s Conflicts and Personality Analysis as the Main Character Portrayed in All The Bright Places - Anak Agung Ayu Istri Kumala Dewi; Ni Made Verayanti Utami; I Wayan Juniartha (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
This research provided an insight into Finch's conflicts and personality as portrayed in the movie All The Bright Places. The qualitative method was used in this research to elaborate and deliver a clear and brief description of the conflicts and his personality as seen through the id, ego, and superego as the major personality structures of humans. The information was gathered by observing Finch's actions and conversations between characters. It was examined using William Kenney's (1966) conflicts theory and Sigmund Freud's psychoanalysis theory (1896). Finch was discovered to be dealing with both internal and external conflict. When Finch tries to control his negative thoughts caused by his abusive father and his environment mocking him, his internal conflict is depicted. Finch versus his father, Finch versus Roamer, and Finch versus society are the external conflicts. The researchers also discovered three main personalities represented by Finch in the movie All The Bright Places, namely the id, ego, and superego.